Towards a Positive Theory of the Determination of Accounting Standards. - Watts, Ross L.; Zimmerman, Jerold L. (The Accounting Review, 1978)
Abstract ABSTRACT: This article provides the beginnings of a positive theory of accounting by exploring those factors influencing management's attitudes on accounting standards which are likely to affect corporate lobbying on accounting standards. Certain factors are expected to affect a firm's cashflows and in turn are affected by accounting standards. These factors are taxes, regulation, management compensation plans, bookkeeping costs, and political costs, and they are combined into a model which predicts that large firms which experience reduced earnings due to changed accounting standards favor the change. All other firms oppose the change if the additional bookkeeping costs justify the cost of lobbying. This prediction was tested using the corporate submissions to the FASB's Discussion Memorandum on General Price Level Adjustments. The empirical results are consistent with the theory.